Withdrawn - Subverting conventional gender-based violence reporting protocols: Clothesline complaints in higher education in Mexico - Masinire, A.; Sanchez-Cruz, E.; Sanchez-Cruz, E. (South African Journal of Higher Education, 2023)
While international conventions with a gender perspective exist, at national level countries such as Mexico have also developed policies and programmes in favour of women’s access to a life of equality and free of violence. Such policies have been translated into institutional protocols to curb gender violence. Despite these polices, data seem to indicate that violence against women continues (UN Women 2020) and gender inequality persists. This article explores the significance of a social gender activist movement that began in 2019 called “clothesline complaints” in one of the most prestigious universities in Mexico. The article also seeks to assess the impact of this movement in other institutions using a documentary analysis research approach. Results show that the selected institutions reported a large number of complaints regarding gender violence. The article concludes that by adopting unconventional grievances reporting procedures of the “clothesline” rather than the traditional institutional protocols, more cases of gender violence can be revealed. We recommend the adoption of the clothesline approach as well as other novel ways of reporting gender-based violence. The clothesline movement presents an opportunity to re-examine the current gender violence reporting structure in higher education institutions in Mexico. Because of the global nature of gender-based violence, we also consider implications for policy and structural review of gender violence reporting protocols in South Africa and other parts of the world. Of key significance is how to integrate informal gender-based violence reports into the formal protocols of reporting without diminishing the original force of appeal which animate the informal reports.